Vliv společenských změn na prosperitu českých lázní - Kraftová, Ivana; Charbuský, Miloš; Šmíd, Martin (Univerzita Pardubice, 2008)
The paper focuses on the influence of social and economic changes upon the spa industry, which is linked with Czech society historically and therefore the legal regulation pays attention to this problem a lot. The objective of this paper is to prove the influence of changes in Czech Republic upon trends in the development of spa industry through selected quantitative descriptors and to evaluate the economic and financial situation of sample of spa economic entities.
Keywords: natural healing spas; Act on Spas; efficiency; Financing; liquidity; profitability